LITERASI REFLEKTIF BERBASIS NARASI LOKAL DI SMPN 1 LOA JANAN KABUPATEN KUTAI KARTANEGARA: Reflective Literacy Based on Local Narratives at SMPN 1 Loa Janan, Kutai Kartanegara Regency - Arifin, M. Bahri; Yohana, Saferi; Prafitri, Wilma (Program Studi Sastra Indonesia Universitas Mulawarman, 2025)
Abstract: This community engagement initiative sought to enhance students' reflective literacy by utilizing local cultural narratives at SMPN 1 Loa Janan, Kutai Kartanegara Regency. The program addressed two primary concerns: the deficiency in students' reflective literacy and the restricted incorporation of local culture in literacy activities. The methodology encompassed five interconnected phases: program socialization and participatory mapping, literacy instruction, creative writing workshops, mentorship, and assessment. Data were gathered by observation, pre-test and post-test assessments, and documentation of students' written assignments. The findings demonstrated a marked enhancement in students' comprehension of narrative structure and their capacity to relate local stories to modern circumstances. Creative writing exercises, such as